2006
DOI: 10.1007/s00170-005-0320-6
|View full text |Cite
|
Sign up to set email alerts
|

Selecting optimal tools for arbitrarily shaped pockets

Abstract: As a result of slicing a 3D part into 2D pockets for generating tool paths, pockets are becoming more commonly used. When a pocket is machined, the question of which of the many feasible tools for cutting the pocket is best always arises. Will cutting be more efficient if multitools are used? Will the algorithm to choose the optimal tools be timesaving enough? This paper presents a method in which an upper bound O(N) is used to choose the optimal cutting tool combination, where N is the number of feasible tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Obviously there will be a higher overhead if more tools are used. It has been demonstrated that the best number of tools should be less than 4 for general cases [13].…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Obviously there will be a higher overhead if more tools are used. It has been demonstrated that the best number of tools should be less than 4 for general cases [13].…”
Section: )mentioning
confidence: 99%
“…In the last work [13], the number of tools selected is restricted to two tools, but the optimal tool combination may exceed two tools. Suppose N different tools are available and feasible, and M is the maximum number of selected tools.…”
Section: Model Of Estimation Of Total Machining Timementioning
confidence: 99%
See 1 more Smart Citation
“…Arivazhagan et al [13] In feature based process planning, features are linked to manufacturing knowledge of various types like machine tool selection, cutter determination, cutting parameters planning. You et al [15] introduced a cutter selection method for pocket feature, and the combination of the optimal tools for the whole machining process of pocket could be generated by simplifying 3D features to 2D boundaries. Banerjee et al [16] described an integrated process planning approach for optimal corner machining which combines the tool path generation and machining parameter selection tasks.…”
Section: Definitions and Applications Of Manufacturing Featuresmentioning
confidence: 99%
“…The use of dynamic SQL and criteria of tool select from database to recognize characteristics of the piece shape in .DXF format is presented by You et al 9 Finally, the case of tool sequence problems by Im and Walczyk, 10 the cutting condition effects as roughness presented by Sarma et al, 11 the prediction of cutting conditions by Gadelmawla et al 12 and path generation are included for milling CNC machines by Eladawi et al 3 The novelty of this research is a new method based on triangulation intersection approach from Poisson's equation applied to automatic selection of the tool CNC mill-lathe machine, showing an easy way to simulate pieces, eliminating the designer subjective decisions, to reduce tool selection mistakes, to make the selection process and to design faster, and hence, it does not require a priori knowledge in operations of milling and turning.…”
Section: Introductionmentioning
confidence: 99%